Hepatitis B reactivation during combination chemotherapy for AIDS-related lymphoma is uncommon and does not adversely affect outcome. - Stebbing,J; Atkins,M; Newsom-Davis,T; Gazzard,B; Bower,M (J Clin Oncol, 2004)
6673 Background: Hepatitis B (HBV) re-activation and susequent liver damage during anti-cancer chemotherapy has been reported in a number of studies. As co-infection with HBV and the immunodeficiency virus-1 (HIV-1) is common, we examined the incidence and degree of HBV re-activation in a cohort of individuals with AIDS-related lymphoma (ARL). METHODS: HBV viral load and surface antigen testing before, during and following cytotoxic chemotherapy with CDE or BEMOP/CA for ARL. RESULTS: Out of 61 individuals tested, 30 were positive for hepatitis B core antibody. All were hepatitis B surface antigen negative and HBV DNA was undetectable prior to chemotherapy. During chemotherapy, re-activation as defined by a detectable HBV DNA was observed in only 5 out these 30 patients (17%) and only 2 demonstrated subsequent surface positive antigenemia. CONCLUSIONS: HBV re-activation during chemotherapy for AIDS-related lymphoma appears uncommon. In HBV surface antigen negative HIV-1 infected individuals with ARL, the risk of HBV related hepatitis during chemotherapy appears insignificant. No significant financial relationships to disclose.